Assessing the characteristics and feasibility of preventing early mortality in patients with hepatocellular carcinoma - Watanabe, Masaaki; Yokomori, Hiroaki; Takahashi, Yoshihito; Okada, Takemichi; Shibuya, Akitaka; Koizumi, Wasaburo (Turkish Journal of Gastroenterology, 2019)
Abstract Background/Aims: To determine strategies to prevent early death (ED) and improve the prognosis of patients with advanced hepatocellular carcinoma (HCC). Materials and Methods: Patients who were diagnosed with HCC from January 2012 to June 2017 were considered for the study. Those who survived for ≤6 months from the date of diagnosis were classified into the ED group (n=21) and those who survived for ≥12 months from the date of diagnosis were classified into the non-ED group (n=88). Results: There were significant differences between the ED and non-ED groups in the following conditions: when the patient age was ≥80 years (38.1% vs. 14.8% patients); maximum nodule size was >3 cm (90.5% vs. 27.3%); Child-Pugh class C liver disease was seen (66.7% vs. 26.1%); tumor-node-metastasis (TNM) Stage III-IV tumor was present (85.7% vs. 21.6%); BCLC stage C/D of liver cancer was seen (81.0% vs. 21.6%); JIS score was ≥4 (52.4% vs. 3.4%); serum creatinine level was ≥1.0 mg/dL (52.4% vs. 22.7%); and there was absence of aggressive treatments such as hepatic resection, radiofrequency ablation, transarterial chemoembolization, and chemotherapy (66.7% vs. 4.5%). Logistic regression analysis identified maximum nodule size of >3 cm (p=0.005, OR=58.7, 95% CI=3.43-1003.9), JIS score of ≥4 (p=0.021, OR=12.0, 95% CI=1.44-100.1), and absence of aggressive treatments (p=0.006, OR=24.7, 95% CI=2.47-247.2) as predictive factors for ED. The presence of aggressive treatments significantly improved the 12-month survival rate of advanced HCC patients with BCLC stage C/D (presence vs. absence: 78.3% vs. 7.4%), a maximum nodule size of >3 cm (76.7% vs. 7.7%), and a JIS score of ≥4 (60.0% vs. 0%). Conclusion: Although delayed detection of HCC strongly increased the onset ED, the aggressiveness of HCC treatment is not readily downgraded, and the most aggressive treatment possible should be considered to prevent ED in patients with advanced HCC. Cite this article as: Watanabe M, Yokomori H, Takahashi Y, Okada T, Shibuya A, Koizumi W. Assessing the characteristics and feasibility of preventing early mortality in patients with hepatocellular carcinoma. Turk J Gastroenterol 2019; 30(6): 541-8.